Association between pressure pain sensitivity, performance stability and overall performance in Olympic sailors - Ballegaard, S.; Petersen, P. B.; Sommer Harboe, G.; Gyntelberg, F.; Faber, J. (Journal of Sports Medicine & Doping Studies, 2016)
Background: During sports competitions, the performance of athletes may be negatively affected by persistent stress and autonomic nervous system (ANS) dysfunction, both of which can be assessed by pressure pain sensitivity (PPS) at the chest bone. Objectives: To test the association between PPS and sports performance; does a reduction of an elevated PPS improve performance stability and overall performance in Olympic sailors? Methods: The case study included two male athletes during eight months of observation prior to and during Olympic sailing. The daily PPS self-measurements served as feedback guide for persistent stress and ANS dysfunction. Performance stability, overall performance and PPS measure were assessed at three intervals. Results: At baseline, the median PPS was 83, the performance stability was inferior to the mean top 10 competitors, and the overall performance was rank eight. During the observation period, PPS, performance stability and overall performance improved incrementally and significantly. This eventually led the sailors to achieve an Olympic Gold. The PPS, performance stability, and overall performance were all internally closely associated (correlation coefficients: r > 0.70; p < 0.001). Conclusion: The study may suggest a link between persistent stress and ANS dysfunction as assessed by PPS on one side and performance stability and overall performance on the other side. (Abstract)